ANALISA WEBSITE MENGGUNAKAN LOAD TESTING PADA SISTEM INFORMASI FILM DENGAN GTMETRIX - Varrel, Shafwan Almer; Musa, Purnawarman; Rachmi, Namira; Fahrurozy, Akbar Rizky; Nugraha, Satria; Sulistiyo, Mukhlisin (Jurnal Simantec, 2024)
Movieku is a free movie download and streaming service that has become a popular choice for users in Indonesia. A smooth user experience requires careful performance testing of the website. This study aims to assess whether the website operates smoothly and provides the best experience for users. Testing was conducted using two techniques: accessing the website with two different devices (a laptop and a mobile device) and comparing performance across various browser applications. The scope of testing includes evaluating website access speed using the GTMetrix tool. The performance test yielded satisfactory response times; however, some aspects of the Movieku website's performance were below average, such as the first contentful paint, which took 1.4 seconds compared to the recommended 0.9 seconds, and the largest contentful paint, which took 2.2 seconds compared to the recommended 1.2 seconds. The study results provide accurate insights into the Movieku website specifically and contribute to optimizing other websites for a smoother and more optimal user experience. Keywords: GTMetrix, Load Testing, Performance Testing, MovieKu Website